Imobilização em filmes LbL de clorofila encapsulada em lipossomos : liberação de fármacos e inativação fotodinâmica - Gorza, Filipe Dione Souza (2014)
In this work, we investigated the chlorophyll (CHL) in its free form or incorporated into liposomes which act as simple systems for drug delivery. The use of the deposition technique layer-by-layer, LBL, allows that structures, such as liposomes, are self-assembled into multilayers alternated with other electrolytes. Multilayers could act as biomolecule immobilization matrix without changing the aqueous environment of the vesicles. The liposomes can be used as membrane mimetic models for studies of the interaction of molecules with biological activities in LBL films. The major advantage of investigating immobilized in LBL film systems is the benefit of characterizing the interaction through available for the substance in solid state techniques. It was possible to immobilize in LBL films, free CHL or incorporated in liposomes. The results indicate that the wettability of the films decreases with increasing number of bilayers and the release of CHL is slow while when incorporated into dipalmitoylphosphatidylcholine (DPPC) occurred more quickly. These are important factors in the practice of controlled delivery of drugs with potential for use in adhesives for transdermal administration. Chlorophyll is commonly used as a drug because of its antibacterial, antioxidant and antigenotoxic action. It has also been used as photosensitizer in photodynamic therapy drug for their high light absorptivity in the visible region of the electromagnetic spectrum. In this paper we investigate the combination of photosensitizer drug chlorophyll, CHL, and laser light (633 nm) for photodynamic inactivation of Candida albicans, responsible for the majority of nosocomial infections that affect immunocompromised individuals. Although complete inactivation has not been reached, the results showed susceptibility to the fungus creep value equals 25.5 J/cm2 and 150 min pre-irradiation. Fluorescence and atomic force microscopy corroborate the results indicating that that the inactivation and cell death must occur due to damage to the cell walls.